Development of Geopolymer Bricks from Synergistic Use of Bagasse Ash and Concrete Residue as an Alternative for Industrial Waste Management - Siriruekratana, Sarocha; Supakata, Nuta (Asian Health, Science and Technology Reports, 2017)
This research studies the feasibility of enhancing the physical and mechanical properties of bagasse-ash-based-geopolymer bricks with concrete residue. The effects of concrete residue were investigated using five different proportions of bagasse ash to concrete residue: 100:0, 90:10, 80:20, 70:30 and 60:40 by weight. A 10 molar concentration of sodium hydroxide and a sodium silicate (Na2SiO3) solution were used as an alkaline solution with a mass ratio of Na2SiO3/NaOH of 2.5. The geopolymer bricks were cured at 65°C for 24 hours in an oven and then at room temperature for 28 days. The chemical composition and particle size distribution of the bagasse ash and concrete residue were then analyzed. Using the TIS 168-2546 specification, the physical and mechanical properties, microstructure and crystal structure of the geopolymer bricks were then tested. The results showed significant improvements in water absorption and compressive strength of geopolymer bricks when concrete residue was added. The maximum compressive strength (8.83 MPa) and the minimum water absorption (0.86%) were found in geopolymer bricks with a 40% concrete residue.